Use of Trawlers for large-scale fishing - Mumbai Archive Project Team (Jio Institute, 2024)
Larger fishing vessels (seen in the backdrop) often use industrial methods to catch fish. The boats, called trawlers, drag large nets known as trawls behind them. There are bottom trawls for fish near the seabed and midwater trawls for fish in the middle of the water column. Trawlers capture large quantities of fish, including shrimp, mackerel, and anchovies.